Versatility of the Keystone Design Perforator Island Flaps in Resurfacing Soft Tissue Defects - Ranjit Kumar Sahu; Kaushik Mahadik; Sanjay Kumar Giri; Santanu Suba; Mainak Mallik; Ritesh Panda; Aparna Kanungo; Reena Minz; Sunil Kumar Rout (Indian Journal of Plastic Surgery)
Background The keystone design perforator island flap (KDPIF) is unique among local flaps because of its high potential for adaptation. We describe our experience with the use of the keystone flap for the reconstruction of a variety of defects in different regions of the body concerning its versatility, surgical outcomes, complications, postoperative pain, operative time, and esthetic outcomes.